2004
DOI: 10.1101/lm.74404
|View full text |Cite
|
Sign up to set email alerts
|

Extending In Vitro Conditioning inAplysiato Analyze Operant and Classical Processes in the Same Preparation

Abstract: Operant and classical conditioning are major processes shaping behavioral responses in all animals. Although the understanding of the mechanisms of classical conditioning has expanded significantly, the understanding of the mechanisms of operant conditioning is more limited. Recent developments in Aplysia are helping to narrow the gap in the level of understanding between operant and classical conditioning, and have raised the possibility of studying the neuronal processes underlying the interaction of operant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 81 publications
0
36
0
1
Order By: Relevance
“…These neurons will be modified by activity-dependent plasticity to bias any future behavior toward the behaviors controlling the heat. Such a process has been found in a similarly isolated behavioral preparation, that is physiologically much more accessible, the operant conditioning of feeding behavior in Aplysia (Nargeot et al, 1997(Nargeot et al, , 1999a(Nargeot et al, , 1999b(Nargeot et al, , 1999cBrembs et al, 2002Brembs et al, , 2004Brembs, 2003aBrembs, , 2003b. In this paradigm, spontaneous bites (or the corresponding neural patterns in the reduced preparation) are rewarded by dopamine-releasing nerve stimulation.…”
Section: Invertebrate Operant Conditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…These neurons will be modified by activity-dependent plasticity to bias any future behavior toward the behaviors controlling the heat. Such a process has been found in a similarly isolated behavioral preparation, that is physiologically much more accessible, the operant conditioning of feeding behavior in Aplysia (Nargeot et al, 1997(Nargeot et al, , 1999a(Nargeot et al, , 1999b(Nargeot et al, , 1999cBrembs et al, 2002Brembs et al, , 2004Brembs, 2003aBrembs, , 2003b. In this paradigm, spontaneous bites (or the corresponding neural patterns in the reduced preparation) are rewarded by dopamine-releasing nerve stimulation.…”
Section: Invertebrate Operant Conditioningmentioning
confidence: 99%
“…Thus, all elements of the three-term contingency are present: BH, CS, and US. The preparation has been shown to produce robust learning effects; it will be interesting to see if results can be found that are analogous to those in Drosophila and, if so, what their neural basis is (Brembs et al, 2004).…”
Section: Invertebrate Composite Operant Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful swallowing is presumably signaled by the esophageal nerves. In other learning paradigms affecting Aplysia feeding, the esophageal nerves have a key role in learning (Nargeot et al 1997(Nargeot et al , 2007Lechner et al 2000;Mozzachiodi et al 2003;Brembs et al 2004;Lorenzetti et al 2006). In both classical and operant conditioning, esophageal nerve stimuli contingent on other stimuli lead to increased feeding.…”
Section: Learning With Edible Foodsmentioning
confidence: 99%
“…Classical and operant conditioning tasks depending on two contingent events affect Aplysia feeding (Nargeot et al 1997(Nargeot et al , 2007Lechner et al 2000;Brembs et al 2002Brembs et al , 2004Mozzachiodi et al 2003;Lorenzetti et al 2006). In these tasks, an unconditional stimulus or a reinforcer from the esophageal nerve is paired with a conditional stimulus or an operant, or with their neural analogs.…”
Section: Cellular Basis Of Learning a Triple Contingencymentioning
confidence: 99%